Investigation of the relationship between childhood traumas, psychological resilience, cognitive flexibility and emotion regulation skills in adults - Güler, Kahraman; Gümüş Demir, Zeynep; Yurtseven, Cansu Selin (The European Research Journal, 2024)
Objectives: This paper looked into the relation between childhood traumas, resilience, cognitive flexibility, and adult emotion regulation skills in adults. Methods: The sample, which is based on the relational screening model, includes 395 participants (female: 202, male: 193). Sociodemographic Information Form, Childhood Trauma Questionnaire, Connor-Davidson Resilience Scale, Cognitive Flexibility Scale and Cognitive Emotion Regulation Questionnaire were applied to the participants to obtain the research data. Data collection was carried out online (google forms) through convenient sampling. The t-test was used to compare the study's quantitative data, and Pearson Correlation analysis was utilized to test the relationship between the scales. Multiple Linear Regression analysis was used for predictive analysis and finally PROCESS was used for mediator role analysis. Results: The investigation's findings revealed that there is a statistically significant difference between the scores of the two groups compared. Findings showed that there is a moderately positive correlation between acceptance and CTQ scores, a weak positive correlation between acceptance and emotional abuse scores, a weak positive correlation with physical abuse scores, a weak positive correlation with physical neglect scores, a weak positive correlation with emotional neglect scores and weak positive correlation with sexual abuse scores. A weak and negative correlation exists between Putting into Perspective and the CTQ, an even weaker and negative correlation exists between Putting into Perspective and the Emotional Neglect and Sexual Abuse scores. Rumination scores have a weak and negative relationship with emotional abuse scores. Conclusions: In order to prevent them from serving as the foundation for difficulties with adult mental health, it is crucial to understand the relationship between traumatic childhood events and psychological resilience, cognitive flexibility, and cognitive emotion regulation techniques. In order to assist people, analyze their thoughts and feelings, be aware of negative coping mechanisms, rigid, inflexible cognitive styles, and negative thinking patterns, clinical psychology practices will benefit from research on these characteristics.